The Role of Parenting Patterns in Shaping Healthy Internet Behaviors for Alpha Generation Teenagers - Dwi Mulyana, Qotrunnada; Muhammad Hadiatur Rahman (Institut Agama Islam Negeri Madura, 2026)
The rapid development of digital technology has made the internet an integral part of Generation Alpha adolescents’ daily lives. While the internet provides educational resources, access to information, and entertainment, uncontrolled use may lead to negative consequences such as digital addiction, exposure to inappropriate content, and reduced social interaction. This study aims to analyze the role of parenting styles in shaping healthy internet behavior among Generation Alpha adolescents in Laden Village, Pamekasan District. The research employed a qualitative descriptive approach involving 10 informants consisting of parents and adolescents selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings indicate that 70% of parents applied an authoritative parenting style, 20% authoritarian, and 10% permissive. Adolescents raised with authoritative parenting demonstrated healthier internet behaviors, such as time management, selective content access, and ethical online interaction. The study concludes that authoritative parenting, characterized by supervision, open communication, and positive role modeling, is the most effective approach in fostering responsible and healthy internet use among Generation Alpha adolescents in rural digital contexts.